Odzyskać Noc: Revisiting the 1990-2000s Anarcho-feminist Protests in Poland as a Strike against Gender-based Violence - Dynda, Barbara (Atlantis)

(untitled) (Mount Saint Vincent University, 2023)
The article analyzes the Polish anarcho-feminist idea of protest against gender-based violence during the late 1990s and early 2000s. Examining the oral history interviews with activists and grassroots cultural productions dating from the period of political transformation, such as zines, leaflets, and graphic images, the article focuses on various strategies and concepts of a feminist strike. These different historical sources emphasize multiple inspirations for the protest strategies employed by the analyzed collectives, including the tradition of women’s strikes during the socialist era, youth demonstrations of the 1960s, and Anglo-American feminism. They also enable revisiting the emotional dynamics and meanings of violence that emerged from the anarcho-feminist archival materials and memories of individual activists.